Neural activity regulates autoimmune diseases through the gateway reflex - Stofkova, Andrea; Murakami, Masaaki (Bioelectronic medicine, 2019)
The brain, spinal cord and retina are protected from blood-borne compounds by the blood-brain barrier (BBB), blood-spinal cord barrier (BSCB) and blood-retina barrier (BRB) respectively, which create a physical interface that tightly controls molecular and cellular transport. The mechanical and functional integrity of these unique structures between blood vessels and nervous tissues is critical for maintaining organ homeostasis. To preserve the stability of these barriers, interplay between constituent barrier cells, such as vascular endothelial cells, pericytes, glial cells and neurons, is required. When any of these cells are defective, the barrier can fail, allowing blood-borne compounds to encroach neural tissues and cause neuropathologies. Autoimmune diseases of the central nervous system (CNS) and retina are characterized by barrier disruption and the infiltration of activated immune cells. Here we review our recent findings on the role of neural activity in the regulation of these barriers at the vascular endothelial cell level in the promotion of or protection against the development of autoimmune diseases. We suggest nervous system reflexes, which we named gateway reflexes, are fundamentally involved in these diseases. Although their reflex arcs are not completely understood, we identified the activation of specific sensory neurons or receptor cells to which barrier endothelial cells respond as effectors that regulate gateways for immune cells to enter the nervous tissue. We explain this novel mechanism and describe its role in neuroinflammatory conditions, including models of multiple sclerosis and posterior autoimmune uveitis.